2020
DOI: 10.1111/jcpp.13201
|View full text |Cite
|
Sign up to set email alerts
|

Rapid neural categorization of angry and fearful faces is specifically impaired in boys with autism spectrum disorder

Abstract: Background: Difficulties with facial expression processing may be associated with the characteristic social impairments in individuals with autism spectrum disorder (ASD). Emotional face processing in ASD has been investigated in an abundance of behavioral and EEG studies, yielding, however, mixed and inconsistent results. Methods: We combined fast periodic visual stimulation (FPVS) with EEG to assess the neural sensitivity to implicitly detect briefly presented facial expressions among a stream of neutral fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 52 publications
(70 reference statements)
3
33
2
Order By: Relevance
“…While some studies have observed impairments in emotion recognition and processing in children with ASD ( 18 , 20 ), to the best of our knowledge, no clear consensus has emerged from the many studies regarding differences in emotion exploration in children with ASD. However, several studies have suggested that “negative” emotions such as fear and anger may be less salient for children with ASD ( 51 53 ). For example, a recent eye-tracking study showed that high-functioning children with ASD perceive fear as less intense than their TD peers ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have observed impairments in emotion recognition and processing in children with ASD ( 18 , 20 ), to the best of our knowledge, no clear consensus has emerged from the many studies regarding differences in emotion exploration in children with ASD. However, several studies have suggested that “negative” emotions such as fear and anger may be less salient for children with ASD ( 51 53 ). For example, a recent eye-tracking study showed that high-functioning children with ASD perceive fear as less intense than their TD peers ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…All data segments were re-referenced to a common average reference. While in frequency-tagging studies we typically apply blink correction (using ICA) for any participant blinking more than 2 standard deviations above the mean (e.g., [ 25 , 92 ], [ 96 ]), in the present study we did not perform any blink correction as none of the participants blinked excessively, i.e., more than two standard deviations above the mean across all participants (0.36 times per second). Note that frequency-tagging EEG yields responses with a high SNR at specific frequency bins, while blink artefacts are broadband and thus do not generally interfere with the responses at the predefined frequency [ 73 ].…”
Section: Methodsmentioning
confidence: 99%
“…This novel tool offers great advantages in terms of objectivity in the identification and quantification of selective responses of interest in the frequency domain of the EEG spectrum, as well as high sensitivity (i.e., high signal-to-noise ratio). A pioneering study by Van der Donck et al (124,125) applied a frequency-tagging EEG oddball paradigm to assess the neural sensitivity for rapid changes in emotional expressions, revealing reduced neural discrimination responses for fearful and angry faces in children with ASD and predicting clinical status with an 87% accuracy at the individual level.…”
Section: Eeg Researchmentioning
confidence: 99%
“…To dissociate these alternatives, EEG paradigms directly contrasting neutral and emotional facial expressions are needed. A particularly promising approach for this would be the administration of a fast periodic visual stimulation oddball frequency-tagging paradigm, as has been applied in ASD (124,125). Thus far, this method has not been applied in primary psychosis, but it was recently administered in patients with velocardiofacial (22q11.2 deletion) syndrome, which is a well-known high-risk group for psychosis (147).…”
Section: Eeg Researchmentioning
confidence: 99%
See 1 more Smart Citation